(untitled) (SAINTEKBU, 2019)
Abstract BKM Sejahtera is a collective leadership institution from a community association in the village of Sumberejo which has the role of mobilizing the potential and resources of the community in an effort to overcome various development issues in the village / village area. BKM Sejahtera still has many obstacles in its operations including the process of making reports and transactions - transactions that occur are still done conventionally, namely the making of reports still using Microsoft Excel as a recording of existing transactions but it is less effective because it requires a relatively long time in presenting reports finance, especially savings and loans and as a storage method, are relatively inefficient because they do not use databases so that they require a large space and difficulties in finding data. The risk of errors in the transaction process and the making of a savings and loan report are relatively high because the data written in the transaction book is sometimes not the same as the data inputted in Microsoft Excel. To overcome the above problems, an Information System Application will be made to the Prosperous Community Self-Help Agency Using the Accrual Basis Method. This application will produce financial reports per period, loan transaction reports, installment transaction reports, savings and loan transaction reports and withdrawal transaction reports. This application is made using a programming language that is PHP for the application interface and MySQL for database processing software. With this application can facilitate transactions and also can facilitate in getting financial reports quickly and have a database as a safe storage medium.